Ventricular Assist Device Patients Have Different Clinical Outcomes and Altered Patterns of Bleeding with Intracranial Hemorrhage. Issue 4 (July 2018) - Ahmed, Mustafa M.; Rahman, Maryam; Neal, Dan; Aranda, Juan M.; Klodell, Charles T.
Abstract : Intracranial hemorrhage (ICH) is one of the most feared complications of left ventricular assist device (LVAD) support. However, outcomes in this group have not been well described. We therefore sought to examine clinical outcomes in this patient population in comparison to those with heart failure (HF) and no LVAD, as well as those without HF or LVAD. The National Inpatient Sample database, years 2002–2012, was queried to classify patients into 3 groups: any ICH (group 1), any HF with any ICH (group 2), and any LVAD with any ICH (group 3). Clinical outcomes, hemorrhage type, neurosurgical intervention rates, and hospital factors were collected and analyzed. Group 1 consisted of 419, 264 patients, group 2 had 41, 186, and group 3 had 118 patients. Group 3 patients were more likely to be in large, academic medical centers, with longer length of stay and higher hospital charges. Inpatient mortality was highest in this group at 39%; however, 46.2% were ultimately discharged to home. Patients in group 3 were more likely to have a subarachnoid or intracerebral hemorrhage versus a subdural or epidural hemorrhage. Neurosurgical intervention rates did not differ between the groups. Although LVAD patients with ICH have worse clinical outcomes, the majority survived their event and nearly half were able to be discharged home. Left ventricular assist device patients also have a distinct pattern of bleeding with ICH. Additional study is required to understand risk factors for the development of ICH in this population and ideal management strategies.